2015
DOI: 10.1159/000368773
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for the Treatment of Refractory Erythema and Flushing of Rosacea

Abstract: Background: Persistent erythema and severe rosacea flushing can cause significant physical discomfort and emotional stress to patients. Currently, no satisfactory treatments are available. Methods: We report two cases of refractory flushing and erythema of rosacea that were successfully treated with intradermal botulinum toxin injections. Results: Good cosmetic results were achieved for both patients. The side effects during and after treatment were mild pain and localized bruising; these symptoms resolved wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 14 publications
0
70
0
1
Order By: Relevance
“…Chemical denervation by botulinum toxin appears to interfere with normal acetylcholine signaling pathways and can provide symptomatic relief to patients with severe facial flushing. Intradermal botulinum toxin injection seems effective and almost a safe therapy for patients with refractory erythema (it may rarely cause headache) and may be considered a reasonable addition to the therapeutic options, especially when other established therapies have failed [9]. …”
Section: Resultsmentioning
confidence: 99%
“…Chemical denervation by botulinum toxin appears to interfere with normal acetylcholine signaling pathways and can provide symptomatic relief to patients with severe facial flushing. Intradermal botulinum toxin injection seems effective and almost a safe therapy for patients with refractory erythema (it may rarely cause headache) and may be considered a reasonable addition to the therapeutic options, especially when other established therapies have failed [9]. …”
Section: Resultsmentioning
confidence: 99%
“…At 4 weeks' follow-up, the quality of life was significantly improved. Botulinum toxin seems an effective therapy also in refractory erythema and flushing in patients with rosacea, as demonstrated in a report of 2 cases by Park et al [84] . The state of the art concerning the role of BoNT-A in these diseases is still debatable, and published studies revealed contrasting results in terms of efficacy.…”
Section: Facial Erythema and Flushingmentioning
confidence: 86%
“…The cheeks, chin, and supra-eyebrow were injected at each session. 66 Improvements in rosacea flushing were evident 1 week after the second treatment and lasted for 3 months. 66,72 The only side-effect reported was mild pain during injection.…”
Section: Medical Developmentsmentioning
confidence: 99%
“…65,66 Frey’s syndrome is a neurological sequel to parotid surgery that causes sweating and flushing whenever saliva production is triggered. 71 These effects may be due to the inhibition by BoNT-A of acetylcholine and vasoactive intestinal polypeptide, and BoNT-A might therefore be an effective treatment for acne and rosacea.…”
Section: Medical Developmentsmentioning
confidence: 99%
See 1 more Smart Citation